3-Ethyl-4-[(E)-2-methylbenzylideneamino]-1H-1,2,4-triazole-5(4H)-thione - Wang, Shan-Heng (International Union of Crystallography, 2008)
Crystals of the title compound, C(12)H(14)N(4)S, were obtained from a condensation reaction of 4-amino-3-ethyl-1H-1,2,4-triazole-5(4H)-thione and 2-methylbenzaldehyde. In the molecular structure, there is a short N=C double bond [1.255 (2) Å], and the benzene and triazole rings are located on opposite sites of this double bond. The two rings are approximately parallel to each other, the dihedral angle being 1.75 (11)°. A partially overlapped arrangement is observed between the nearly parallel triazole and benzene rings of adjacent molecules; the perpendicular distance of the centroid of the triazole ring from the benzene ring is 3.482 Å, indicating the existence of π–π stacking in the crystal structure.